2014
DOI: 10.1017/s027226311400059x
|View full text |Cite
|
Sign up to set email alerts
|

Number Attraction Effects in Near-Native Spanish Sentence Comprehension

Abstract: Grammatical agreement phenomena such as verbal number have long been of fundamental interest in the study of second language (L2) acquisition. Previous research from the perspective of sentence processing has documented nativelike behavior among nonnative participants but has also relied almost exclusively on grammar violation paradigms. The present investigation examined the online comprehension of subject-verb number agreement by native and nonnative speakers of Mexican Spanish using the more subtle agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 42 publications
5
35
0
Order By: Relevance
“…Consistent with previous work on agreement attraction that has identified an asymmetry between number features in determining agreement attraction (Bock & Miller 1991;Bock & Eberhard 1993;Vigliocco et al 1995;1996;Vigliocco & Nicol 1998;Bock et al 2001;Hartsuiker et al 2003;Alcocer & Phillips 2009;Bock et al 2012;Acuña-Fariña et al 2014;Jegerski 2016), we found that native speakers of Spanish exhibit clear effects of attraction for number: ungrammatical sentences with a singular NP1 but plural NP2 and ADJ were rated higher than other cases of ungrammaticality. Also consistent with the previous literature, we failed to find evidence of attraction for gender.…”
supporting
confidence: 91%
“…Consistent with previous work on agreement attraction that has identified an asymmetry between number features in determining agreement attraction (Bock & Miller 1991;Bock & Eberhard 1993;Vigliocco et al 1995;1996;Vigliocco & Nicol 1998;Bock et al 2001;Hartsuiker et al 2003;Alcocer & Phillips 2009;Bock et al 2012;Acuña-Fariña et al 2014;Jegerski 2016), we found that native speakers of Spanish exhibit clear effects of attraction for number: ungrammatical sentences with a singular NP1 but plural NP2 and ADJ were rated higher than other cases of ungrammaticality. Also consistent with the previous literature, we failed to find evidence of attraction for gender.…”
supporting
confidence: 91%
“…However, incongruency, that is, ungrammaticality in the use of epistemic may, has slightly different consequences: as can be seen in the "Results" section, there was a significant interaction between congruency and segment with the start of reading slowdown on segment 3, which then continued on segment 4, with an effect at segment 5, just short of significance using the adjusted alpha value. This is in line with SPR studies that have investigated the impact of syntactic violations and ungrammaticality on readers' reaction times in milliseconds (e.g., Hopp, 2006Hopp, , 2016Jegerski, 2012Jegerski, , 2016Pliatsikas & Marinis, 2013). Support for the immediacy assumption is obtained here even more convincingly.…”
Section: Discussionsupporting
confidence: 85%
“…The current study used a SPR task because the SPR paradigm has been extensively exploited in research measuring native and nonnative sensitivity to morphosyntactic violations, syntactic or semantic ambiguity, and pragmatic plausibility (e.g., Hopp 2006Hopp , 2016Jegerski, 2012Jegerski, , 2016Marinis, 2003;Mifka-Profozic, 2017;Pliatsikas & Marinis, 2013;Roberts & Felser, 2011;Roberts & Liszka 2013, Stewart et al, 2009aTokowicz & Warren, 2010). Research on monolingual sentence processing has provided evidence that native speakers vary their reading times on a word-by-word basis and adjust their reading depending on the properties of each word such as the length, frequency, and/or word complexity (Just et al 1982;Keating & Jegerski, 2015).…”
Section: Self-paced Reading Studies and Online Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include reading time data from post-stimulus comprehension questions, as very few studies have done this (see, e.g.,Jegerski, 2016).8 This included obligatory and optional instantiation. Coding decisions were uncontroversial except in the case of one featureplural number markingin four studies, which we specify here: We considered plural number marking to be cross-linguistically different for Chinese learners inChan (2012) andJiang (2004Jiang ( , 2007, and for Japanese learners inJiang et al (2011).…”
mentioning
confidence: 99%